Experimental Optimization of the Compound Angled Asymmetric Laidback Fan Shaped Film Cooling Hole - Ye Rim Jo; Jin Young Jeong; Jae Su Kwak (Energies, 2022)
In this study, the effect of shape variables on the film cooling effectiveness of the compound angled asymmetric laidback fan shaped hole was experimentally investigated, and the optimum values of select design variables were presented. Among the shape variables of the compound angled asymmetric laidback fan shaped hole, the windward and leeward lateral expansion angles and the compound angle were selected as design variables. Test points were chosen using the central composite design method, and the selected design variables were optimized using the Kriging model. The film cooling effectiveness was measured using the PSP technique, and the experiment was conducted under the two density ratios of 1.5 and 2.0 and four blowing ratios of 1.0, 1.5, 2.0, and 2.5. Experimental results showed that the film cooling performance was improved for higher density ratios than lower density ratios. The main effects analysis indicated that larger windward and leeward lateral expansion angles induced higher film cooling effectiveness; however, the compound angle did not show consistent results. For the optimized hole at the density ratio 2.0, the results indicated that the overall averaged film cooling effectiveness of the optimized compound angled asymmetric laidback fan shaped hole was higher than that of the optimized fan shape holes of previous literature.